Noncitizenism Recognising Noncitizen Capabilities in a World of Citizens - Bloom, Tendayi (2017)
Noncitizens have always been present in liberal political philosophy. Often hard to situate within traditional frameworks that prioritise citizenship, noncitizens can appear voiceless and rightsless, which has implications for efforts towards global justice and justice in migration. This book proposes an alternative. Noncitizenism identifies an analytical category of noncitizenship. While maintaining the importance of citizenship, noncitizenship is another form of special individual-State relationship. It operates far from a State, at its borders, and within its territory, providing a tool for examining the continuity between sites of engagement and the literatures, questions, and conclusions relating to them. The book argues that an accurate liberal theoretical framework, and one which can address contemporary challenges, must acknowledge the political relationship of noncitizenship between individuals and States. This book is for students and scholars of political philosophy and for those interested in noncitizenship and how it can inform the response of liberal theory, citizenship, global justice, migration studies, political theory and policy work.